Behavioural intention towards online grocery services in Melaka / Muhammad Nasrun Syahmi Baharun - Baharun, Muhammad Nasrun Syahmi (Faculty of Business and Management, 2019)
Since the late 1980s, the online grocery has been around and adopted in regions such as Europe, Australia and Asia. The online grocery trend has been inflamed by the growth of the Internet and now the smart device era. Advanced technology, including Internet technology, is used to communicate, search for information, easily text and send e-mails to anyone worldwide. There are many factors that influence the consumers’ actual usage of e-grocery. This dissertation studies Malaysian consumers and why some of them are willing to use e-grocery, while some do not. Therefore, the research had been conducted to study the behavioural intention of consumers towards online grocery services by determining the factors influence it. The independent variables that had being examined in this study are perceived usefulness, perceived ease of use, perceived risk and social influence that influencing consumers’ behavioural intention towards online grocery. Questionnaires had been distributed to 200 respondents at shopping mall around Melaka City and the respondents are being selected using convenience sampling and 200 target respondents successfully being return and valid questionnaires. Social Sciences (SPSS) for Statistical Package had been employed for data analysis on descriptive, correlation and regression analysis. Based on results, the research objectives and research questions have been answer which is to identify level of behavioural intention on online groceries products, to identify the most influence factors that affect behavioural intention on online groceries products and to identify relationship between perceived usefulness, perceived ease of use, perceived risk, social influence and behavioural intention on online groceries products.